The Embryonic Development of the Giant Freshwater Mountain Crab, Isolapotamon bauense Ng, 1987 - Jongkar, Grinang; Lirong, Yu Abit; ANNIE, CRISTIANUS; Mohd Salleh, Mohamad Amran (Malaysian Fisheries Society, 2022)
The embryonic development of the giant freshwater mountain crab, Isolapotamon bauense Ng ,1987 endemic to Sarawak, Malaysia which is an endemic species listed as Vulnerable under the IUCN redlist, is described for the first time in this paper. Mature female I. bauense were observed to spawn small clutches of large macrolecithal eggs typical of other potamid primary freshwater crabs. Embryonic development occurred within the eggs corresponding to other primary freshwater crabs. The developing embryo goes through 3 major development stages within the egg before hatching into a fully formed crab hatchling at the end of the gestation period. Eggs had a gestation period of between 36-45 days from spawning until hatching. The findings of the present study provide useful insight into the life cycle and breeding biology of I. bauense which will be applicable for both conservation and aquaculture studies in the future.